A proposed air-conditioning system using fuzzy algorithm for industrial application - Sarker, Md. Shakowat Zaman; Leng, Chan Yin; Bhuyan, Mohammad Shaharia; Islam, Md. Shabiul; Othman, Masuri (IEEE, 2006)
This paper describes the development of a novel air condition control system based on fuzzy logic. A fuzzy logic air conditioning controller with two inputs and one output has been designed with an industrial application in mind. This system consists of two sensors for feedback control: one to monitor temperature and another one to monitor humidity. There are three control elements: cooling valve, beating valve, and humidifying valve, to adjust the temperature and humidity of the air supply. A fuzzy rule for this controller is formulated by temperature and humidity. The model of this controller has been tested using MATLAB simulation.